Civil Procedure in Malaysia - Abu Hanifa Mohamed Abdullah , Shahrul Mizan Ismail (International Law Book Service, 2016)
this book prepares students by challenging them to use the law that they learn in class while also explaining the best way to express an answer in law school exams.